Influence of phenyl-attached substituents on the vibrational and electronic spectra of meso-tetraphenylporphyrin: A DFT study - Ngaojampa,C. (Elsevier BV, 2015)
© 2015 Elsevier B.V. The effects of substituents attached to phenyl groups of free base meso-tetraphenylporphyrin (H2TPP) on its geometrical structure, vibrational spectra and electronic spectra of H2TPP derivatives namely FB1-8 are predicted by the density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations. The calculations revealed no notable changes in the geometrical structures of the substituent-altered H2TPP derivatives. Changes in the vibrational modes are mainly observed in the phenyl moieties of the porphyrin molecules, and less significant in the central porphine ring except for two derivatives, FB4 and FB8. The substituent effects have more influence on the electronic structures of the studied porphyrins. The introduction of strong electron-donating and - withdrawing substituents, i.e. dimethylamino and nitro groups in this study, to the four phenyl rings results in the splits in the Soret or B band of the derivatives due to a major rearrangement in energy levels of the molecular orbitals. The dimethylamino groups (in FB4) dramatically increase the Q band intensities of the molecule. The intensified Q bands are the results of strong charge-transfer from the substituents to the porphine core upon the electronic excitations. Among the eight designed dyes, FB4 is promising to be further developed as metalloporphyrin-based dye. The understandings of the electronic structure and optical properties according to the molecular modifications are useful in the rational design of the zinc-porphyrin-based sensitizer in the solar cells.